(untitled) (Journal of Advanced Veterinary and Animal Research, 2022)
Objectives: This study was designed to examine the effects of various concentrations of tris (hydroxymethyl) aminomethane (tris) and egg yolk on the quality of cryopreserved buck sperm. Materials and Methods: The collected semen samples were pooled, washed, and diluted into five different freezing extender groups, viz., extender I (tris 0% + egg yolk 0%), extender II (tris 1.41% + egg yolk 4%), extender III (tris 2.41% + egg yolk 8%), extender IV (tris 3.41% + egg yolk 16%), and extender V (tris 4.41% + egg yolk 24%). The sperm parameter of the five groups of extenders was evaluated after equilibration and cryopreservation. Results: The results showed that extenders II–V provided significantly higher semen progressive motility and total motility percentages than extender I after equilibration (p < 0.05). The higher percentages of semen progressive motility, total motility, viability, and plasma membrane integrity (by both HOST under light microscopy and stain after HOST under light microscopy) were found in the sperm cryopreserved with extender IV than extender I, extender II, and extender III groups after thawing (p < 0.05). In addition, semen progressive motility, total motility, and viability were not further increased, or plasma membrane integrity (by both HOST tests) was decreased by the addition of tris and egg yolk (extender V) after cryopreservation (p < 0.05). Conclusion: In conclusion, our result indicatesthat the following washing, the supplementation of tris (3.41% + egg yolk 16%) on the freezing extender are suitable for improving the semen quality of buck after freezing and thawing. J. Adv. Vet. Anim. Res., 9(4): 676–683, December 2022 http://doi.org/10.5455/javar.2022.i636